Pink guava juice pasteurisation: Fouling deposit and cleaning studies - Ho, Ai Ling; Tan, V. C.; Norashikin, Ab. Aziz; Farah Saleena, Taip; Mohd Nordin, Ibrahim (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/